Processing poultry feathers into keratin hydrolysate through alkaline-enzymatic hydrolysis - Mokrejs, Pavel; Svoboda, Petr; Hrncirik, Josef; Janacova, Dagmar; Vasek, Vladimir (Waste management & research., 2011)
Poultry feathers make up for as much as 8.5% of chicken weight and represent a considerable amount of almost pure keratin waste which is not being adequately utilized at the present time. The present study dealt with the processing of poultry feathers through a two-stage alkaline-enzymatic hydrolysis. In the first stage, feathers were mixed with a 0.1 or 0.3% KOH water solution in a 1 : 50 ratio and were incubated at 70°C for 24 h. After adjusting pH to 9, the effects examined in the second processing stage on the amount of degraded feathers were those of proteolytic enzyme additions (1-5%), time (4-8 h) and temperature (50-70°C). Processing feathers in 0.3% KOH and hydrolysing for 8 h in the second stage at 70°C with a 5% dose of enzyme (relative to dry feathers weight) produced approx. 91% degradation. Keratin hydrolysate is distinct for its high nitrogen content and reasonable inorganic solids level. Two-stage technology of alkaline-enzymatic hydrolysing of poultry feathers in an environment of 0.3% KOH achieves high efficiency under quite mild reaction conditions (temperature not exceeding 70°C with pH in a mildly alkaline region), and is feasible from an economic viewpoint. Keratin hydrolysate can find particular application in packaging technology (films, foils and encapsulates).
Keywords: drůbež; Animals; Feathers; hydrolýza; teplota; Hydrogen-Ion Concentration; Keratins; Poultry; Industrial Waste; keratiny; průmyslový odpad; Refuse Disposal; proteasy; Temperature; Peptide Hydrolases; peří; Hydrolysis; odpadky - odstraňování; zvířata; koncentrace vodíkových iontů